ANALYSIS OF ILLOCUTIONARY ACT IN THE PRINCE AND THE PAUPER MOVIE - Suci Almuslimah (English Department, Faculty of Humanities, Andalas University, 2012)
This research deals with an analysis of Illocutionary Act in The Prince and the Pauper movie. There are two primary objectives in this study; first, to find the types of the illocutionary act in The Prince and the Pauper movie and second, to find the dominant type used in this movie. In collecting the data, the writer uses non participant observational method purposed by Sudaryanto (1993). In this study, the writer applies Searle’s theory (1979) and Ibrahim’s theory (2003) in the analysis. The analysis of illocutionary act was also supported by the theory of context proposed by Leech (1983). As the result, the writer finds there are five types of illocutionary act in the utterances occur in the movie. They are, assertive, directive, commissive, expressive, and declaration. The writer also finds that directive is the dominant type being used in the movie.